Support farmer-to-farmer and community-wide social learning - Shikuku, Kelvin Mashisia; Mwongera, Caroline; Läderach, Peter R.D.; Acosta, Mariola; Ampaire, Edidah L.; Eitzinger, Anton; Lamanna, Christine; Mwungu, Chris Miyinzi; Twyman, Jennifer; Winowiecki, Leigh Ann (International Center for Tropical Agriculture, 2017)
Research suggests that farmer-to-farmer learning can be up to six times more effective in spreading knowledge of CSA practices than in areas where it is not carried out. Understanding the wider context and requirements for social learning is key. Peer learning is an effective way to disseminate CSA knowledge based on trust, relying on social networks, with learning and social multiplier effects. Together with collective action, it can lead to effective adoption of CSA practices. Such farmer-to-farmer learning can usefully reinforce – and be reinforced by – extension and other change agents. For it to work, farmer-to-farmer learning requires performance incentives and rewards.